UJI VALIDITAS ISI MODUL â€œFINGER PAINTINGâ€ UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS SEBAGAI PERSIAPAN KEMANDIRIAN MENGGOSOK GIGI ANAK DOWN SYNDROME DI SLB SRI SOEDEWI: CONTENT VALIDITY OF THE â€œFINGER PAINTINGâ€ MODULE TO ENCHANE FINE MOTOR SKILLS AS A PREPARATION FOR THE INDEPENDENCE OF TOOTBRUSHING FOR CHILDREN WITH DOWN SYNDROME AT SLB SRI SOEDEWI - Sayyidatina Salsabila Putri; Marlita Andhika Rahman; Annisa Andriani (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2023)
ABSTRACT Introduction The activity of brushing teeth is necessary to maintain dental and oral hygiene. This is a crucial matter for all individuals, including those with down syndrome. During tooth brushing, fine motor skills such as finger dexterity and hand flexibility are required. Obstacles in fine motor aspects in children with down syndrome can lead to difficulties in performing such activities. Therefore, efforts are needed to stimulate fine motor skills, one of which is by providing activities like finger painting. This is the reason behind the development of the